Prediction of methane production performances based on determination of organic components for different vegetable wastes - Cai, Fanfan; Yan, Hu; Zhang, Ruihong; Liu, Guangqing; Chen, Chang (International Journal of Agricultural and Biological Engineering, 2019)
The rapid development of the economy has led to rapid consumption of fossil fuels, which results in extremely serious environmental problems. Biomass energy has been accepted as a way to reduce the usage of fossil fuels due to its cleanliness and renewability. In this study, vegetable wastes (VWs), an abundant kind of biomass resource, were treated by anaerobic digestion (AD) to be converted into methane. The total solids (TS), volatile solids (VS), elemental contents, and organic components of 17 kinds of typical VWs were systematically determined. The methane production performances were then measured and ranged from 120.1 mL/g VS (for pepper stem) to 377.7 mL/g VS (for bok choy). To easily and quickly predict the methane yields of VWs, a curvilinear relationship between different organic compositions (e.g., cellulose, hemicellulose, lignin, non-structural carbohydrate, protein, and VFA contents) and methane production was established and proved to be a useful tool for methane prediction. Four kinetic models (first-order model, Fitzhugh model, Cone model, modified Gompertz model) were applied to simulate the process of AD, and Cone and modified Gompertz models were shown to describe the AD process well. This study will not only provide basic data about the characteristics and methane production of 17 kinds of VWs but also contribute a method for predicting the methane yields of vegetable wastes, which is also valuable in future agro-industrial applications.Keywords: naerobic digestion, organic components, methane production, vegetable waste, kinetic modelsDOI: 10.25165/j.ijabe.20191203.4705Citation: Cai F F, YanH, Zhang R H, Liu G Q, Chen C. Prediction of methane production performances based on the determination of organic components for different vegetable wastes. Int J Agric & Biol Eng, 2019; 12(3): 154–159.